2022
DOI: 10.3389/fchem.2022.814643
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Adsorption and Removal of Heavy Metals Based on Polyamide-amines Composites

Abstract: In recent years, the problem of heavy metal pollution has become increasingly prominent, so it is urgent to develop new heavy metal adsorption materials. Compared with many adsorbents, the polyamide-amine dendrimers (PAMAMs) have attracted extensive attention of researchers due to its advantages of macro-molecular cavity, abundant surface functional groups, non-toxicity, high efficiency and easy modification. But in fact, it is not very suitable as an adsorbent because of its solubility and difficulty in separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…Heavy metal decontamination of polluted water with aid of dendritic polymeric materials is influenced by pH due to its impacts on the moieties on the surface of dendritic polymer. Furthermore, solution pH plays a crucial role in the adsorption performance of dendritic polymeric materials by altering the speciation and shape of metal ions [29,40]. The mercury (Hg) adsorption onto silica gel-supported salicylaldehyde-modified PAMAM dendrimers was investigated using the density functional theory (DFT) approach in another study [41].…”
Section: Environmental Remediation Using Dendritic Polymersmentioning
confidence: 99%
“…Heavy metal decontamination of polluted water with aid of dendritic polymeric materials is influenced by pH due to its impacts on the moieties on the surface of dendritic polymer. Furthermore, solution pH plays a crucial role in the adsorption performance of dendritic polymeric materials by altering the speciation and shape of metal ions [29,40]. The mercury (Hg) adsorption onto silica gel-supported salicylaldehyde-modified PAMAM dendrimers was investigated using the density functional theory (DFT) approach in another study [41].…”
Section: Environmental Remediation Using Dendritic Polymersmentioning
confidence: 99%
“…19 Nevertheless, these methods have the disadvantages of high cost and complicated operation. 20 Compared with these, the adsorption method is not only inexpensive and simple to operate but also have no pollution to the environment. The adsorption method is through the interaction between the adsorbent and the dyes to achieve the removal of the dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to treat dyes including the membrane separation method, , extraction method, , radiation method, , oxidation method, ultrasonic degradation method, coagulation sedimentation method, magnetic separation method, and so on . Nevertheless, these methods have the disadvantages of high cost and complicated operation . Compared with these, the adsorption method is not only inexpensive and simple to operate but also have no pollution to the environment.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Therefore, researchers often fix them on various substrates to remove heavy metal ions from wastewater. 13 Some studies have confirmed that appropriate surface chemical modification is an effective strategy to improve the interaction between adsorbents and related adsorbates. The existing literature reports that the adsorption of Hg(II) can be significantly increased by the modification of sulfur-containing substances (e.g., mercaptans, sulfide, and sulfonated substances) or the presence of sulfur on the surface of the adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…H-PAMAMs have the advantages of a low production cost and a short production cycle, making them economically suitable for large industrial applications . However, there is a non-negligible problem that they are soluble and difficult to separate when they are used directly as adsorption materials. , Therefore, researchers often fix them on various substrates to remove heavy metal ions from wastewater . Some studies have confirmed that appropriate surface chemical modification is an effective strategy to improve the interaction between adsorbents and related adsorbates.…”
Section: Introductionmentioning
confidence: 99%